The Indonesia’s Urgency on Adopting New Approach on Comprehensive Prevention in Countering Terrorism Strategy: Lesson Learnt from the Mako Detention Facility’s Riot and East Java Bombs - Amaritasari, Indah P. (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2018)
Indonesia was confronted with a series of terror attacks in May 2018, among others: riot incidents accompanied by police hostage by terrorist prisoners at Mako Brimob Prison in Kelapa Dua, Depok on May 8, 2018, a suicide bombing occurred in three churches simultaneously on Sunday morning, 13 May, suicide bombing at the entrance of Polrestabes Surabaya on May 14th. This series of events shows that terrorism remains a security threat in Indonesia. Several terror attacks in Indonesia are believed to have been committed by terrorist groups baited to ISIS. Indonesia in the context of countermeasures against acamanism has used a number of approaches both soft approach and hard approach by using the criminal justice model. Nevertheless, Indonesia has modified the criminal justice approach by involving the role of the military. Therefore, it is necessary to understand the various forms associated with the hard approach. and how do new strategies also need to be considered looking at existing threats? This paper attempts to explore possible new strategies adopted by Indonesia as a continuation of the UN response to the problem of violent extremism. This paper is a further development of the research results of the Center for National Security Studies (Puskamnas) Bhayangkara Raya University of Jakarta is on the global map of terrorism.